Teacher’s Belief in Online Learning during Pandemic Covid-19: Learner’s Need - Vina Fathira; Hermawati Syarief; Sitti Hadijah (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2022)
The researchers need in evaluating teacher’s belief in teaching EFL learners by online learning during pandemic. Online learning is different from face to face learning so that the researcher interested in doing this research. The aim of the research is about teacher’s belief in doing online learning for EFL learner during pandemic covid-19. The descriptive research was conducted in this research. There were 18 EFL teachers randomly filled the questionnaire distributed in Google form. To collect the data, all teachers were asked to fill the 12 questions of questionnaire. Next, to analyze the data, the researcher made some analysis based on questionnaire about teacher’ belief in online learning. In this research, the result indicated that teacher’s belief about the planning of online learning from analyzing learner’s need. It can be seen from most of the teachers give response “agree and strongly agree” in understanding the aim, operating the online media, in analyzing learner’s need in supporting online learning.